2017
DOI: 10.5812/jhealthscope.64184
|View full text |Cite
|
Sign up to set email alerts
|

A survey on Measles and Rubella Supplementary Immunization Activities (SIAs) in Iran

Abstract: Background: Supplementary Immunization Activities (SIAs) have been considered as a strategic key towards elimination of measles and rubella. This study aimed at identifying the coverage of vaccination in target population children. Methods: The study was carried out in South-East of Iran on a total of 6838 randomly selected children. Information was collected by trained interviewers using a validated questionnaire. The data was analyzed through descriptive statistics (i.e. frequencies and percentages) and 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The subnational coverage of measles and supplemental immunization activities (SIAs) for target age group should be done annually in high risk and very high risk districts that have poor surveillance quality. However, based on recent research in Iran this index was 98.7% [9] . Rapid and wide progress regarding to elimination and eradication of measles was conducted in Iran [11] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The subnational coverage of measles and supplemental immunization activities (SIAs) for target age group should be done annually in high risk and very high risk districts that have poor surveillance quality. However, based on recent research in Iran this index was 98.7% [9] . Rapid and wide progress regarding to elimination and eradication of measles was conducted in Iran [11] .…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the trend in MCV1 and MCV2 coverage and high coverage of immunization beside the minimum of dropout rates from MCV1 to MCV2 and dropout rates from MCV1 to first dose of DPT0 or Pentavalent vaccine are important factors for low overall risk of measles in Iran. Recent studies in Iran showed that there are some documentations for elimination of measles [ 7 , 9 , 10 , 11 , 18 , 20 ]. The subnational coverage of measles and supplemental immunization activities (SIAs) for target age group should be done annually in high risk and very high risk districts that have poor surveillance quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iran is one of the countries in the Eastern Mediterranean Region (2). During the past years, the routine immunization coverage was increased and the surveillance system data were improved and, consequently, the disease incidence decreased (3)(4)(5)(6)(7). Thus, the endemic virus transmission have ______________________________ Corresponding author: Dr Hossein Ansari, ansarih@razi.tums.ac.ir 1 ↑What is "already known" in this topic: During the past years, the routine immunization coverage of measles was increased and the surveillance quality was improved.…”
Section: Introductionmentioning
confidence: 99%